Pengembangan Bahan Ajar Biologi Berbasis Sains, Technology, Environment, and Society (Stes) untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SMA Islam 1 Surakarta - Khotim Nurma Indah; Soetarno Joyoatmojo; Suharno Suharno (Universitas Sebelas Maret, 2016)
The objectives of this research are: 1) to know the condition of biology learning material on SMA Islam 1 Surakarta; 2) to know the procedure of developing the learning materialsfor Biology based on STESfor the students of SMA Islam 1 Surakarta;3) to know the effectiveness of the learning materials based on STESto improve the student’s critical thinking skills of SMA Islam 1 Surakarta. The research used the Research and Development (R&D) method, which referred to the model claim by Borg & Gall, and which was modified into nine phases, namely: 1) research and information collecting; 2) planning; 3) development preliminary form of product; 4) preliminary field testing; 5) main product revision; 6) main field testing; 7) operational product revision; 8) operational field testing; and 9) final product revision. The respondents of learning materials development included field testing respondents consisting 2 validators, limited-scale main field testing respondents consisting 10 students, and operational field testing respondents consisting of 23 students. The data of research were gathered through questionnaire, observation, in-depth interview, and test. They were analyzed by using the descriptive qualitative method. Meanwhile, the result of critical thinking skill was analyzed by using normalized N-gain and Paired Sample T test to investigate the effectiveness of the Biology’s learning materials based on STES to improve student’s critical thinking skills. The results of research are as follows: 1) Biology learning materials on SMA Islam 1 Surakarta has been used in learning process are less facility to improve critical thinking skills; 2) The development procedure began with first design, then continue with a media and material expert validation in order to show that learning material for Biology based on STES is appropriate for the trial;3) The results of the effectiveness of the developed Biology learning materials based on STES to improve crtitical thinking skills are indicated by the improvement of scores critical thinking skill that was analyzed by normalized N-Gain and Paired Sample T-Test, each result are 0,40 and 0,008. Based on the results of research a conclusion is drawn that Biology’s learning materials based on STES are effective to improve student’s critical thinking skills.